Evaluating stakeholder‐derived strategies to reduce the risk of ships striking whales. Issue 10 (16th July 2019) - Redfern, Jessica V.; Moore, Thomas J.; Becker, Elizabeth A.; Calambokidis, John; Hastings, Sean P.; Irvine, Ladd M.; Mate, Bruce R.; Palacios, Daniel M.
Abstract: Aim: Ship strikes are one of the largest sources of human‐caused mortality for baleen whales on the West Coast of the United States. Reducing ship‐strike risk in this region is complicated by changes in ship traffic that resulted from air pollution regulations and economic factors. A diverse group of stakeholders was convened to develop strategies to reduce ship‐strike risk in the Southern California Bight. Strategies proposed by some stakeholders included: (a) adding a shipping route; (b) expanding the existing area to be avoided (ATBA); and (c) reducing ship speeds. Location: Southern California Bight, off the coast of California, United States. Methods: We developed methods to estimate ship traffic in the stakeholder‐derived strategies using 8 years of ship traffic data. To assess ship‐strike risk for fin, humpback, and blue whales, we used habitat models developed from 7 years of survey data and home ranges derived from 53 blue whale tags. We defined collision risk as the co‐occurrence between whales and ships. The risk of a lethal collision was calculated by multiplying collision risk by the probability that a collision is lethal, which is estimated using ship speed. Results: Speed reductions resulted in a large decrease in the risk of a lethal ship strike. Creating a shipping route or expanding the ATBA reduced the risk of a strike by removing traffic from a whale feeding area. Creating a shipping route was opposed by the United States Navy and the shipping industry, but expanding the ATBA was broadly supported. Main conclusions: Our analyses suggest that speed reductions and expanding the ATBA may provide an optimal solution for addressing stakeholder needs and reducing ship strikes in the Southern California Bight. The methods we developed can be used to address the global issue of balancing human use of the marine environment with the protection of whale populations.